Highly Active Ni- and Co-Based Bimetallic Catalysts for Hydrogen Production From Ammonia-Borane - Furukawa, Shinya; Nishimura, Genki; Takayama, Tomoaki; Komatsu, Takayuki (Frontiers in Chemistry, 2019)
Ammonia-borane is one of the promising candidates for hydrogen carrier. A series of Ni- and Co-based bimetallic catalysts supported on SiO2 (Ni–M/SiO2 and Co–M/SiO2; M = Ga, Ge, Sn, Zn) were prepared and tested as catalysts for hydrogen production from ammonia-borane (AB) in water or methanol. Ni–Zn/SiO2 and Co–Ge/SiO2 exhibited catalytic activities much higher than those of monometallic Ni/SiO2 and Co/SiO2, respectively. Ni–Zn/SiO2 showed a high catalytic activity when water was used as a solvent, where the reaction was completed within 6 min at room temperature with the specific reaction rate of 4.3 ml min−1 mmol-cat−1 mM-AB−1. To the best of our knowledge, this is the highest value among those reported using 3d-metal-based catalysts. Co–Ge/SiO2 afforded a five times higher reaction rate than that of the corresponding monometallic Co/SiO2. XRD, TEM, and HAADF-STEM-EDS analyses revealed that Ni0.75Zn0.25 and Co0.8Ge0.2 solid-solution alloys were formed with high phase purities. An XPS study showed that Co atoms in Co0.8Ge0.2 were electron-enriched due to electron transfer from Ge to Co, which may be the origin of the improved catalytic activity.